Jawabanmu

2013-12-06T20:34:09+07:00
Subsitusi; x+2y=1
              y-x=-4
    y= -4+x
 x+2(-4+x)=1
x+-8+2x=1
3x=9
x=3 
               x= -2y+1
         y - ( -2y+1)= -4
         y+2y-1= -4
        3y= -3
          y= -1
gabungan;  (x+2y=1) x1= x+2y=1
                 (y-x= -4) x2=2y-2x= -8 
                                       3x=9
                                          x=3
 y-1(3)= -4                                         spldv= (3,-1)
 y-3= -4                                          
     y= -1